'Educational' Deprivation is Associated with PD Peritonitis. Issue 4 (July 2018) - Khalid, Usman; Zaidi, Aeliya; Cheang, Adrian; Horvath, Szabolcs; Szabo, Laszlo; Ilham, Mohamed A.; Stephens, Michael R.
Background: Socioeconomic deprivation is an important factor in determining poor health and is associated with a higher prevalence of many chronic diseases, including renal failure, and often poorer outcomes for patients with such conditions. The aim of this study was to investigate the effect of deprivation on peritonitis episodes following peritoneal dialysis (PD)-catheter insertion. Methods: The Welsh Index of Multiple Deprivation (WIMD) was used to assess the influence of socioeconomic deprivation on outcomes following 233 consecutive first PD-catheter insertions from a single institution in the United Kingdom, performed between 2010 and 2015. The primary outcome measure was the presence of peritonitis episodes. Results: Peritoneal dialysis catheters were inserted in 243 patients, of which data were available for 233. Fifty-four patients experienced at least 1 episode of peritonitis. Overall, more patients in the most deprived group (vs least deprived) experienced peritonitis, although this was not statistically significant. When analyzing the severity of the peritonitis, within the 'Education' domain of the WIMD, significantly more patients from the most deprived group (compared with the least deprived group) experienced '2 or more peritonitis' episodes ( p = 0.04) and were hospitalized for antibiotics ( p = 0.02). Conclusion: This study has shown that patients who live in more 'educationally' deprived areas are more likely to have multiple episodes of peritonitis requiring hospital admission following PD-catheter insertions.